Traditional Jamu Trough Theme of Spices in Conceptual Still Life Photography - Tanrere, Rezki Gautama (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2024)
Development of technology filled with various visual media storytellings, especially photography, makes not only photographers who create still life photography works, but those involved in art and visual storytellers participate in exploring this genre which can be an effective medium for storytelling. Still life photography that prioritizes layout, properties and lighting based on the creator's idea, aims in expressing emotions because it provides flexibility in arrangement its composition elements. The purpose of this study focuses on still life photography which not only move objects into a photo, but contain meaning, messages and an artistic photo results. The research method by qualitatively through sample observation and literature theory, through the theme of spices represented in jamu as a characteristic of Indonesian identity and culture, the results can show that conceptual still life photography can become a powerful visual media in introducing Indonesian wealth of culture and agricultural. The implication is that still life photography through this theme is not just displaying objects, but creating a space for artistic experiment, understanding traditions and cultural, and providing a new dimension to everyday objects that are often overlooked in modern life.